Lemmus sibiricus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Lemmus sibiricus (Kerr, 1792). In Linnaeus, Anim. Kingdom, p. 241. TYPE LOCALITY: Russia, Yamalo-Nenetskaya Nats. Okr., between Polar Ural Mtns and lower course of Ob River. DISTRIBUTION: Holarctic tundra landscapes: in Palearctic, from White Sea, W Russia, to Chukotski Peninsula, NE Siberia, and Kamchatka; including Nunivak and St. George islands in the Bering Sea; in Nearctic, from W Alaska east to Baffin Island and Hudson Bay, and south in the Rocky Mtns to C British Columbia, Canada. SYNONYMS: alascensis, bungei, chrysogaster, flavescens, harroldi, helvolus, iterator, kittlitzi, minor, minusculus, nigripes, novosibiricus, obensis, paulus, phaiocephalus, portenkoi, subarticus, trimucronatus, xanthotrichus, yukonensis. COMMENTS: North American races revised, as L. trimucronatus, by Davis (1944) and retained as such by Hall and Cockrum (1953) and Hall and Kelson (1959). Rausch (1953) proposed the synonymy of trimucronatus and nigripes under Old World L. sibiricus, a taxonomic arrangement elaborated by Rausch and Rausch (19751?) and maintained in subsequent faunal works (Banfield, 1974; Hall, 1981; Jones et al., 1986). Gileva (1983) and Gileva et al. (1984) believed that the cytogenetic peculiarities of chrysogaster confirm its independence as a species relative to L. amurensis, L. lemmus, and L. sibiricus , and suggested it may be conspecific with North American L. trimucronatus . The sample they identified as chrysogaster, however, comes from the Chukotski Peninsula on the coast of the East Siberian Sea, not from the west coast of the Okhotsk Sea, the type locality of chrysogaster. Pavlinov and Rossolimo (1987) retained, with reservation, chrysogaster in the synonymy of L. sibiricus pending further study and accurate identification of lemmings from the Chukotski Peninsula. Corbet and Hill (1991) continued to recognize the St. George Island form nigripes as a species. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World ...